Suitability and Carrying Capacity Analysis of Marine Tourism in Merak Kecil Island - Putri, Amelia Herdani; Sasongko, Agung Setyo; Cahyadi, Ferry Dwi; Prasetiyo, Himawan (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2024)
Merak Kecil Island is an emerging marine tourism destination in Cilegon City, encompassing an area of 0.76 hectares, located in the waters of the Sunda Strait within Pulomerak District. This research was conducted over a one-month period, from January to February 2024, involving three sampling stations. The study aimed to analyze tourism suitability parameters, calculate the area's carrying capacity, and develop strategies for ecotourism development on Merak Kecil Island, Cilegon City. Data collection was carried out through field observations and measurements of regional parameters, including environmental, physical, and chemical data. These were supplemented by data analysis utilizing the Tourism Suitability Index (TSI), Carrying Capacity (CC) calculations, and a SWOT analysis derived from interviews conducted via questionnaires. The results indicated that the Tourism Suitability Index for recreational activities was 86% at Station 1, 84% at Station 2, and 78% at Station 3, all of which fall under the category of